Association between placental epigenetic age acceleration and early postnatal growth patterns - Priyadarshni Patel; Angela Shen; Cynthia Perez; Elizabeth M. Kennedy; Kartik Shankar; Kevin J. Pearson; Aline Andres; Todd M. Everson (Scientific Reports)
Abstract Placental gestational age acceleration (GAA) is the difference between the actual gestational age (GA) at birth and their estimated epigenetic gestational age (EGA), which is calculated from placental DNA methylation. Understanding the role of placental GAA in postnatal growth trajectories is crucial for early identification of infants at risk of altered growth patterns and associated long-term health outcomes. The objective of this study is to investigate the association between placental GAA and longitudinal growth trajectories specifically weight, height, fat mass, and lean mass gain in early childhood. This study uses placental DNA methylation at birth to calculate epigenetic GAA and longitudinal measures of weight, height, fat mass, and lean mass to generate growth trajectory characteristics. Higher placental GAA was significantly associated with slower weight gain (95% CI [− 0.03, − 0.001]) and fat mass (95% CI [− 0.08, − 0.02]) gain, as well as reduced average fat mass (95% CI [add this]) over the follow-up period. However, no significant associations were found between GAA and height or lean mass gain. Placental GAA can give early insights into altered postnatal growth trajectories, particularly for weight and fat mass where an increase in GAA is associated with decreased weight and fatmass gain over time while we observed no effect on height and lean mass. Understanding these associations offers insights into early developmental patterns and long-term health outcomes in children, highlighting the importance of perinatal factors in shaping growth trajectories in early childhood.